Karakteristik Elektrik Implementasi Membran Kitosan-Karagenan dan Jembatan Garam pada Microbial Fuel Cell Menggunakan Substrat Limbah Singkong Terfermentasi Yeast - Ferina Srinurfitri; Amir Supriyanto; Gurum Ahmad Pauzi; Junaidi Junaidi (Departement of Physics, Faculty of Mathematics and Natural Sciences, University of Lampung, 2022)
A Microbial Fuel Cell (MFC) is an electrochemical system that generates energy utilizing waste as a substrate and the results of microbial metabolism processes. This research utilizes yeast fermented cassava waste as a substrate to determine the electrical characteristics of PEM in the form of a chitosan-carrageenan membrane and salt bridge. The cassava waste is from the waste produced in the manufacture of tapioca flour. A dual-chamber MFC made of acrylic with a size of 8x8x10 cm is used. Cassava waste substrate with carbon electrodes would be in the anode compartment, and seawater electrolyte with Cu(Ag) fiber electrodes would be in the cathode compartment. Each measurement holds ±250 ml in each compartment. The MFC system consists of 10 cells and is analyzed every hour for 120 hours using a multitester. According to the results of the research, cassava waste (liquid and onggok) can be used as a substrate in the MFC system, which has the potential to produce alternative electrical energy. Compared to salt bridges, the use of PEM in the form of chitosan-carrageenan membranes produces more significant and better electrical characteristics. However, the chitosan-carrageenan membrane is still less suitable in the long term than the salt bridge.